Characterization and pathogenicity of coconut cadang-cadang viroid variants in oil palm (Elaeis guineensis jacq.) seedlings - Joseph, Hendry (2012)
Coconut cadang-cadang viroid is considered a threat to the oil palm industry. It is associated with an orange spotting (OS) disorder in oil palm but its pathogenicity has never been confirmed. Therefore this study was to establish Koch’s postulate of CCCVd variants characterized from oil palm. Detection of CCCVd-like RNAs in oil palm was enhanced with optimized Natrium Chloride EDTA Tris-HCL mercaptoethanol (NETME) extraction and dot blot hybridization using full-length digoxigenin (DIG)-labelled CCCVd246 cRNA probe. Nucleic acid sequenced from a known CCCVd positive symptomatic (SRD6) and asymptomatic (SRH2) oil palm from Selangor contained a variant of 246 nt (CCCVd OP246). The presence of oil palm CCCVd variant was also confirmed in Sabah when a symptomatic oil palm (SBH4) was found with CCCVd OP246. Sequence analysis showed that CCCVd OP246 obtained from Selangor (SRD6, SRH2) and Sabah (SBH4) were identical and had 97% sequence similarity with CCCVd246 of coconut. Partially purified nucleic acid extract of SRD6 and SRH2 were inoculated into oil palm pre-germinated seedlings and tissue culture plantlets. CCCVd-like RNAs were detected by dot blot hybridization, six months after inoculation in all pre-germinated seedlings and in tissue culture plantlets except for seedling P2-5 (pre-germinated seedling) and control (Milli-Q water inoculated) seedlings and plantlets. Pre-germinated seedlings and tissue culture plantlets that were inoculated with SRD6 nucleic acid extract were shorter with more fronds compared to those inoculated with SRH2 nucleic acid extract and control (Milli-Q water). All ten pre-germinated seedlings inoculated with SRD6 nucleic acid extract showed OS symptom on the leaf, 9 months after inoculation meanwhile 2 of 10 pre-germinated seedlings inoculated with SRH2 nucleic acid extract showed OS symptoms at 12 months after inoculation. All three tissue culture plantlets that were inoculated with SRD6 nucleic acid showed OS symptom on the leaf at 6 months after inoculation Meanwhile all five tissue culture plantlets inoculated with SRH2 nucleic acid extract did not show any OS symptom,raising the possibility of host resistance against CCCVd variants especially in tissue culture plantlets as pre-germinated seedlings inoculated with SRH2 nucleic acid extract showed OS symptoms in two seedlings. Symptom appearance was faster in tissue culture plantlet compared to pre-germinated seedling. RT-PCR, cloning and sequencing at 12 months after inoculation revealed that the old and young frond of the inoculated oil palm pre-germinated seedlings and tissue culture plantlets contained CCCVd OP246 identical in sequence to the symptomatic (SRD6) and asymptomatic (SRH2) oil palms from the field that were used as inoculums in this study, therefore fulfilling Koch’s postulate. Lack of sequence variation between fielda and inculated CCCVd OP246 from both symptomatic (SRD6) and asymptomatic (SRH2) oil palms suggests that sequence variation may not be vital in symptom expression of CCCVd oil palm variant. This reports for the first time that oil palm CCCVd OP246 is the causal agent of OS in oil palm and replicates autonomously in its host either expressing symptoms or in a symptomless manner.